Quarter Life Crisis Akibat Kebingungan Karier (Pengalaman Hidup Mahasiswa Akhir UNSIKA dalam Perspektif Fenomenologi) - Hana Amelia; Tri Susanto; Oky Oxygentri (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
Quarter-life crisis is an emotional state commonly experienced by individuals in the emerging adulthood phase, namely the age range of 18–25 years, especially among final-year students. This condition is characterized by the emergence of anxiety, fear, confusion, and uncertainty regarding the future, particularly in achieving and determining career direction. The phenomenon of quarter-life crisis is generally felt when students are in the final stage of higher education and begin to face the realities of life after college, such as the demands of immediately entering the world of work and determining career choices that align with personal interests, abilities, and expectations. Uncertainty about job opportunities often triggers feelings of doubt and psychological stress. This study aims to determine the meaning of quarter-life crisis due to career confusion in final-year students, and explore their experiences in dealing with this condition. This study uses a qualitative approach with Edmund Husserl's phenomenology method to understand the subjective experiences of informants in depth. The Symbolic Interactionism theory of George Herbert Mead and Herbert Blumer is used as a theoretical basis in analyzing the meaning-making process carried out by students. The results show that final-year students have diverse experiences and meanings in dealing with quarter-life crisis due to career confusion. This meaning is formed through intrapersonal communication processes, such as self-reflection and inner dialogue, which influence how individuals interpret environmental demands and the uncertain future they face.